ACUTE GASTROENTERITIS IN CHILDREN - Bojadzieva, Sonja; Sofijanova, Aspazija; Jordanova, Olivera (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
The aim of the study was to investigate the most frequent etiology of AGE in children admitted аt our hospital, and the correlation with severity of clinical manifestation. The study was designed as a prospective study, and we examined 219 pediatric patients with AGE admitted at the University Children’s Hospital–Skopje. The diagnosis of AGE was based by the definition for AGE as a decrease in the consistency of stools (loose or liquid), and/or an increase in the frequency of evacuations (typically >3 in 24 hours), with or without fever or vomiting. The stool specimens were examined using the new multiplex polymerase chain reaction–based rapid diagnostic test–Film Array Gastrointestinal panel test. White blood cell levels (10^3/ul) and hemoglobin levels (g/dL), were determined by using the flow citometry method on Sysmex xs 800i/1000i. Iron levels (µmol/L) were determined by using the biochemistry analyzer Architect c4000 Abbott. Statistical analysis confirmed significantly different values of stool isolation: viruses and bacteria in the groups  p<0.001. The stool parasites were insignificant p>0.05. Statistical analysis confirmed significantly different values ​​of WBC levels in the groups  p<0.001. Statistical analysis confirmed significantly different values of iron levels in the groups  p<0.001. Statistical analysis confirmed significantly different values of h​emoglobin levels in the groups p<0.001. Film Array Gastrointestinal panel test is a useful tool in the rapid diagnosis of gastrointestinal pathogens in pediatric patients with acute gastroenteritis.  Keywords : Acute gastroenteritis (AGE), pediatric patients immunocomtentence, pediatric patients, immunocompromised, Film Array Gastrointestinal panel test. https://doi.org/10.55302/JMS2143040b